PELATIHAN PENGELOLAAN EVENT KESENIAN BANTENGAN DI DESA TULUS BESAR - Pritantina Yuni Lestari; Hilda Cahyani; Sugeng Hariyanto; Tri Astuti Handayani; Dhimas Dwi Nugraha Hadistya; Mutia Dewi Hidayati (Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program is designed to address the needs of the community of Tulus Besar Village, Tumpang District, in enhancing their capacity to manage Bantengan art events within the Tulus Besar tourism village area. The program involves local art practitioners to increase tourist visits, both domestic and international. The participants of this training are Bantengan art practitioners from Tulus Besar Village.Through this program, participants are expected to gain improved knowledge and skills in managing Bantengan art events, from the planning stage to the actual implementation of the events in Tulus Besar Village. The program will be carried out in seven stages: (1) planning (to identify the number of participants involved and the training materials required), (2) socialization, (3) coordination with village authorities and art practitioners (to ensure that the proposed plan aligns with community needs), (4) training, (5) mentoring, (6) monitoring and evaluation, and (7) publication.